Fortune Falls - Goebel, Jenny (Scholastic Press, 2016)
In Fortune Falls, where superstitions are real, and all children must pass regular "luck tests" to see if they are worthy, ill-fortuned Sadie has always been deemed as unlucky, and shunted aside for her luckier younger brother--but when she finds an unusually intelligent black cat named Jinx, her fortunes begin to change for the better.